Clinical Features, Replication Competence, and Innate Immune Responses of Human Adenovirus Type 7 Infection. (25th August 2020) - Chen, Qigao; Liu, Jun; Liang, Weiwen; Chen, Yi; Dou, Min; Liu, Zhongmin; Chen, Yuan; Zheng, Zhongli; Zhu, Bing; Lin, Yongping
Abstract: Background: Epidemiologic reports suggest that the most severe or fatal adenoviral disease in children might be associated with human adenovirus (HAdV) type 7. However, the pathogenesis of HAdV-7–induced severe disease remains poorly understood. Methods: HAdV-3 and HAdV-7 replication kinetics and the host response to infection were compared using ex vivo human lung tissue cultures. Furthermore, cytokine and chemokine levels and the presence of adenovirus DNA in the serum of hospitalized children infected with HAdV-7 (n = 65) or HAdV-3 (n = 48) were measured (using a multiplex immunoassay and Taqman real-time polymerase chain reaction, respectively). Results: Among 471 HAdV-positive specimens, HAdV-3 or HAdV-7 was the most prevalent genotype during 2014–2016 or 2018, respectively. The incidence of severe pneumonia was higher in HAdV-7–infected than in HAdV-3–infected individuals (30.1% vs 4.5%, respectively). HAdV-7 replicated more efficiently than HAdV-3 ex vivo. Interferon-induced protein 10, interleukin 6, and monocyte chemoattractant protein 1 levels were significantly higher in HAdV-7–infected than in HAdV-3–infected children. Adenovirus DNA was detected in serum samples from 40% and 4.2% of HAdV-7– and HAdV-3–infected children, respectively. Furthermore, viremia was strongly associated with severe clinical presentations. Conclusions: The pathogenesis of HAdV-7–induced severe disease was probably associated with high replication competence and hyperinflammatory responses. The detection of adenovirus DNA in blood may be useful in assessing risk for severe disease. Abstract : This study investigated the pathogenesis of severe or fatal adenoviral diseases caused by human adenovirus type 7 (HAdV-7) in children. HAdV-7 was found to be associated with high replication competence and hyperactive cytokine-mediated inflammatory response, which leads to severe disease.